Potential of vermicompost drippings and other vermicomposting products on the growth and yield of lettuce - Besas, Ulysses P.; Caniones, Sinneth; Aceres, Larry V. (2020)
Vermicompost drippings (VD), one of the by-products of vermicomposting, have been largely ignored in the Philippines as an organic fertilizer for economically important vegetable crops. Several reports mention that using vermicompost drippings/leachates have significantly improved crop growth, which had been attributed to its large amounts of plant nutrients, growth hormones, and presence of beneficial organisms. This study aims to look into the potential of vermicompost drippings as a possible foliar fertilizer for lettuce. The application of vermicompost drippings, vermitea, and vermicompost significantly improved growth, yield and nutrient uptake of lettuce grown in acidic soil conditions, which is comparable with those fertilized by synthetic fertilizers. Further improvement in yield was recorded when vermicompost was supplemented with a foliar application of vermicompost drippings. In terms of nutrient uptake, a tripled increase from plants treated with at least two vermicomposting products was recorded while highest phosphorus uptake was manifested by the application of vermicompost drippings. The same trend exists in potassium plant uptake, where there was an observed increase of about four times potassium content in tissue compared to the control. This increased nutrient resulted in taller and heavier plants with bigger and more developed leaves, dramatically increasing yield. Hence, lettuce could be grown organically using vermitea, vermicompost, and vermicompost drippings, but further improvement of growth and yield could be done using a combined application of vermicompost and drippings.
Keywords: Vermicompost Leachate; Vermicomposting; Lettuce growing; Mindanao studies